Agent-Based Service-Oriented Computing - Griffiths, Nathan; Chao, Kuo-Ming.; SpringerLink (Online service) (London : Springer London, 2010)
Distributed software systems are becoming evermore prevalent, and we increasingly desire them to operate in heterogeneous, dynamic, and open environments. Service-oriented computing (SOC) has emerged over recent years as a successful approach for building and maintaining such systems. However, as the environments in which we require systems to operate become more complex, we require software components to have increasing degrees of flexibility, autonomy, and intelligence. Agent-based systems naturally complement SOC by offering the intelligence and reasoning capabilities that are needed. The integration of agents and SOC is a broad and active research area. This book is a collection of chapters from experts in the field, that gives an overview of the state-of-the-art in the main areas of current research, and identifies likely future directions. Researchers, students and practitioners will find this book a useful insight into the current state-of-the-art. The book also includes a general introduction the basic notions of SOC for readers who are unfamiliar with the approach.
Service Advertisement and Discovery -- Multi-Agent Coordination for Service Composition -- Flexible Workflow Management in Service Oriented Environments -- Semantics for Service-Oriented Architectures -- Dependability in Service-Oriented Computing -- Consensus Issues for Service Advertisement and Selection -- Trust and Reputation -- QoS-Aware Service Selection -- Future Directions.
Keywords: Computer science; Software engineering; Information storage and retrieval systems; Electronic data processing; Information Systems; Computer Science; Models and Principles; Software Engineering; Management of Computing and Information Systems; Computing Methodologies; Information Storage and Retrieval; e-Commerce/e-business.